Utilizacion del Lactosuero,en la alimentacion de Pollos Broiler con raciones bajas en proteinas (13% y 15%), en etapa de acabado para obtencion de Pollivapos (8-11 semanas) - Romero Garcia, Cesar (2012)
The following thesis have title “USE THE LACTOSUERO, IN THE SUPPLY OF CHICKENS BROILER WITH LOW SHARES IN PROTEINS (13 % and 15 %), IN STAGE OF ENDED FOR POLLIPAVOS OBTAINING ( 8 - 11 weeks)”.; With the aim to contribute to the knowledge of new forms of supply, more efficient and economical of chickens for meat (broiler); in the Region San Martin; It was realized in the district of the Band of Shilcayo, area of the Center of Agricultural Production “Miraflores”, Faculty of Agrarian Sciences of the National University of San Martin, Located in the area "Ahuashiyacu"; the zone presents an average annual rainfall of 1213 mm / year. Everage temperature of 26.2°C, maxim of 28°C and minim of 34°C; also a Relative Dampness of 78.5 %. Used the Design completely at random (DCA), with three treatments and two repetitions. The treatments were To: (18 % of P.T), T1: (13 % of P.T), T2: (15 % of P.T). The results demonstrated that major profit and economic benefit generated the treatment T2 (15 % P.T) showing us S/'s clear usefulness. 490.89 and clear profitability of 28.93 % to comparison with other treatments T0 (20 % P.T) and T1 (13 % P.T) with S/'s clear usefulness. 484.33 S/. 423.99 and clear profitability of 26.81 % and 25.56 %. Observing these values, we can affirm that the use of lactosuero as food supplement for the upbringing chicken Broiler, for Pollipavos obtaining offers economic positive benefit. Allowing to manage reduce n the supply of chickens broiler, as well as it is possible to replace the use of the fish meal as source of protein, since the lactosuero improves the utilization of the protein of vegetable sources, since it is the case of the cake of soy bean.